Potentiation of Chemical Ototoxicity by Noise - Steyger, Peter S. (2009)
High-intensity and/or prolonged exposure to noise causes temporary or permanent threshold shifts in auditory perception. Occupational exposure to solvents or administration of clinically important drugs, such as aminoglycoside antibiotics and cisplatin, also can induce permanent hearing loss. The mechanisms by which these ototoxic insults cause auditory dysfunction are still being unraveled, yet they share common sequelae, particularly generation of reactive oxygen species, that ultimately lead to hearing loss and deafness. Individuals are frequently exposed to ototoxic chemical contaminants (e.g., fuel) and noise simultaneously in a variety of work and recreational environments. Does simultaneous exposure to chemical ototoxins and noise potentiate auditory dysfunction? Exposure to solvent vapor in noisy environments potentiates the permanent threshold shifts induced by noise alone. Moderate noise levels potentiate both aminoglycoside- and cisplatin-induced ototoxicity in both rate of onset and in severity of auditory dysfunction. Thus, simultaneous exposure to chemical ototoxins and moderate levels of noise can potentiate auditory dysfunction. Preventing the ototoxic synergy of noise and chemical ototoxins requires removing exposure to ototoxins and/or attenuating noise exposure levels when chemical ototoxins are present.